The associations between caffeine treatment and common preterm morbidities: a retrospective cohort analysis - Yavanoglu Atay, Funda; Kanmaz Kutman, Hayriye Gözde; Bidev, Duygu; Bozkurt Kalyoncu, Özlem; Oğuz, Şerife Suna (Frontiers in Pediatrics, 2023)
Caffeine is one of the most used drugs in NICUs. It is widely regarded as beneficial in preventing many morbidities by reducing apnea of prematurity and improving respiratory functions. Methods: Premature infants with gestational ages > 25 and < 32 weeks who were hospitalized in the NICU between 2008 and 2013 and survived to discharge were retrospectively analyzed. Infants treated with prophylactic caffeine were compared with historical controls born in 2008 and did not get caffeine treatment. Maternal and neonatal characteristics and common neonatal morbidities were recorded. Results: A total of 475 patients were analyzed. Patients receiving caffeine were classified as Group 1 (n=355), and patients not receiving caffeine were classified as Group 2 (n=120). Despite the higher incidence of RDS requiring surfactant therapy and a longer duration of respiratory support in Group 2, the rates of BPD and most other common morbidities were quite comparable. The frequency of apnea was statistically lower in the group that received caffeine prophylaxis (p<0.01). Conclusion: In this retrospective cohort analysis, we found that caffeine prophylaxis significantly decreased apnea attacks however does not prevent respiratory morbidity such as BPD.